THE STUDY OF ENGLISH PHONOLOGICAL ERRORS OF ADVANCED SECOND LANGUAGE LEARNERS IN PRONOUNCING SIMILARLY-SPELLED WORDS - Dangin, Dangin; Wijayanti, Nurvita (Lire Journal (Journal of Linguistics and Literature), 2018)
The phenomenon of phonological error as the common sense in pronouncing the words not only happens among beginners but also among the advanced English learners. The English learners are also active speakers who use English as their second language used such as in a formal situation. They tend to pronounce the same for words that have same spelling as other words in most parts of the words or even thewhole words but of different parts of speech. The present writers’ study tries to answer the question on how the English learners’ pronunciation is influenced by words with the same spelling. The participants of the study were Indonesian college students who learned English at the advanced level. In order to get the data, they were given word lists that contained a number of words and then asked to pronounce them. These words were suspected as common mistakes pronounced by the advanced learners. For example the word ‘determine’ is pronounced the same as the word ‘mine’, the word ‘preface’ is pronounced as ‘face’. In this study, the result reveals that the English learners tend to pronounce the words that refer to other words that contain the same orthography. Orthographically, the words and part of the words have the same spelling but they do not share the same pronunciation. Therefore, this error is commonly found among English learners even among those of the advanced level.